Development of an EOG (Electro-Oculography) Based Human-Computer Interface - Ding, Qiuping; Tong, Kaiyu; Li, Guang (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
We designed an inexpensive user computer interface for helping the disabled persons to communicate with their caretakers, which is based on EOG (electro-oculography) signals rather than the very expensive reflectance based methods. EOG signals of different eye movement patterns are analyzed with the LOS guiding setting constructed ourselves. An effective eye movement pattern is found to control the computer. Testing conducted on 12 subjects show that this system is remarkably accurate, easy to operate and reliable